Mean oscillation and boundedness of multilinear operator related to multiplier operator - Zhao Qiaozhen (De Gruyter, 2021)
In this paper, the boundedness of certain multilinear operator related to the multiplier operator from Lebesgue spaces to Orlicz spaces is obtained.